Introducing Lotus 123 - Bradley, Helen (Helen L. C.) (Brisbane : John Wiley and Sons, 1996)
This book is about: Working with worksheets; Editing a worksheet; Formating a worksheet; Getting help with Lotus; ...
Keywords: Lotus 1-2-3.; Business; Lotus 1-2-3 (Computer file); Business -- Computer programs; Electronic spreadsheets